2017
DOI: 10.1007/s00404-017-4548-9
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity focused ultrasound (HIFU) treatment for uterine fibroids: a meta-analysis

Abstract: These results suggest that HIFU treatment of uterine leiomyomas leads to clinical improvement with few significant clinical complications and adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…During myomectomy, the continuity of the normal myometrium was interrupted, and the formation of myometrial scars, which were strained and thinner than the normal myometrium, may exert a negative effect on uterine contractions and increase the risk of uterine rupture during pregnancy and labor [26,27]. HIFU ablation treatment for uterine fibroids is a noninvasive tissue ablation technique with similar efficacy, faster recovery, and fewer complications compared to myomectomy [14,28]. During treatment, an ultrasound probe is used to provide real-time imaging of the patient's anatomy surrounding the uterus and to monitor the thermal effect of the ablation on the targeted fibroids.…”
Section: Pregnancymentioning
confidence: 99%
“…During myomectomy, the continuity of the normal myometrium was interrupted, and the formation of myometrial scars, which were strained and thinner than the normal myometrium, may exert a negative effect on uterine contractions and increase the risk of uterine rupture during pregnancy and labor [26,27]. HIFU ablation treatment for uterine fibroids is a noninvasive tissue ablation technique with similar efficacy, faster recovery, and fewer complications compared to myomectomy [14,28]. During treatment, an ultrasound probe is used to provide real-time imaging of the patient's anatomy surrounding the uterus and to monitor the thermal effect of the ablation on the targeted fibroids.…”
Section: Pregnancymentioning
confidence: 99%
“…High-intensity focused US has increasingly been used for treatment of uterine fibroids worldwide because of its excellent therapeutic efficacy in producing symptomatic relief. 26,27 It has been revealed that HIFU has a therapeutic effect on uterine fibroids mainly by causing coagulation necrosis of targeted tissue, which was presented as a nonenhancement characteristic on enhanced MRI. 28,29 Enhanced MRI was considered an important evaluation measure for the early therapeutic response of uterine fibroids to HIFU.…”
Section: Discussionmentioning
confidence: 99%
“…Among various opinions on MRgFUS/MR-HIFU method, attention is particularly focused on satisfactory clinical efficacy, quick recovery and very low morbidity [36,37,40]. The method is generally safe as side effects occur rarely [36,[40][41][42][43].…”
mentioning
confidence: 99%
“…Among various opinions on MRgFUS/MR-HIFU method, attention is particularly focused on satisfactory clinical efficacy, quick recovery and very low morbidity [36,37,40]. The method is generally safe as side effects occur rarely [36,[40][41][42][43]. MRgFUS/MR-HIFU-derived adverse effects include different kinds of skin burns, fever, nausea, tiredness, pain, blood clot formation or transient nerve palsy due to prolonged stationary position [43][44][45].…”
mentioning
confidence: 99%
See 1 more Smart Citation